Evaluation Implementation Differentiation in Learning Mathematics for Students Elementary School - Rina Agustina; Nita Erviana; Sowiyah Sowiyah (Foundation of Jannatun Naim Lampung, 2025)
In implementing curriculum independence, results study show that The, lack of variation methods used by teachers in learning mathematics causes low motivation and interest in students. The fact is a show that in learning mathematics the differentiation Is only in progress in one aspect of the process. Research objectives This is To describe implementation differentiation in learning mathematics for students' school basics. Research This is a type of study qualitative descriptive with a method survey. The subject study was chosen using purposive sampling and assigning 6 people as data sources. The instrument used is a questionnaire with a distribution questionnaire as a data collection technique. Stages Data analysis using Miles and Huberman's steps, namely: data reduction, data presentation, and data extraction. Conclusion. Based on the results data analysis can concluded that in learning mathematics for students school base Already applies aspect differentiation in matter namely : (1) preparation, (2) implementation, and (3) assessment. In the preparation process, the aspects The differentiation used by teachers is in determining the design of learning and questions the test used. In addition, it was also carried out initial diagnostic test For known differentiation that is owned by students. In the implementation process, aspects of differentiation used​ that is the implementation of the learning process which includes different styles of learning and characteristics of other students. In the assessment process, aspects of differentiation used​ are question tests that include several type-level difficulties and bait customized returns​ with characteristics of students.